The adult knee knee arthroplasty - Rubash, Harry E. (Wolters Kluwer, 2021)
"As knee replacement surgeries continue to grow in number worldwide, the need for an authoritative and comprehensive reference in this key area is a must for today's orthopaedic surgeon. The Adult Knee: Knee Arthroplasty, Second Edition, brings together the knowledge and expertise of internationally recognized experts in the field in one convenient volume. Covers knee biomechanics relevant to knee arthroplasty, alternatives to knee arthroplasty to alleviate arthritis, and primary total knee arthroplasty, including perioperative issues. Discusses complications including stiff knee, periprosthetic fractures, and instability, revision total knee arthroplasty, and management of infections in total knee replacement"--